Quando o poeta toma partido : literatura e política em Mansueto Bernardi - Marinello, Adiane Fogali (My University, 2014)
The aim of this research is to investigate the literary and political project of Mansueto Bernardi (1888-1966), through comprehensive analysis of his literary and historiographic essays, as well as of his speeches and poems. Having published only one literary work, the author had nevertheless intense cultural and political activity in the first half of twentieth century. Besides creating and supervising periodicals at Livraria e Editora Globo, in Porto Alegre, he served in both the federal and the Rio Grande do Sul state governments, having achieved the position of Chairman of the Brazilian Mint (Casa da Moeda) during President Getúlio Vargas administration. This study attemps to demonstrate that Bernardi tried to make the culture of Rio Grande do Sul known and made considerable efforts to divulge the creed of Catholicism in Brazilian society, therefore placing religion as a main source for his literary and political project. This Dissertation constitutes an interdisciplinary approach that reports the findings of research involving Literature, History and Sociology, while focusing regional culture.
Esta Dissertação investiga o projeto literário e político de Mansueto Bernardi (1888-1966), através da interpretação e análise dos seus ensaios literários e historiográficos, discursos e poemas. O autor, apesar de ter editado uma única obra literária, Terra convalescente, teve intensa atuação cultural e política durante a primeira metade do século XX, criando e dirigindo periódicos da Livraria e Editora Globo, de Porto Alegre, atuando em funções administrativas dos governos estadual e federal, chegando, inclusive, a chefiar a Casa da Moeda, durante o governo de Getúlio Vargas. Desse modo, este estudo tenta mostrar que Bernardi procurou divulgar a cultura do Estado do Rio Grande do Sul e esforçou-se para difundir o catolicismo na sociedade brasileira, colocando, em virtude disso, a religião como linha norteadora de seu projeto literário e político. Trata-se, portanto, de uma discussão interdisciplinar que transita entre a Literatura, a História e a Sociologia, e se volta para a cultura regional.
Keywords: Sociolingüística e dialetologia; Literatura sul-rio-grandense; Crítica literária; Política; Literatura; Cultura regional; Literature sul-rio-grandense; Literary critics; Politics; Literature; Regional culture; Bernardi, Mansueto, 1888-1966